2004
DOI: 10.1291/hypres.27.327
|View full text |Cite
|
Sign up to set email alerts
|

A High Prevalence of Gitelman's Syndrome Mutations in Japanese

Abstract: Although Gitelman's syndrome (GS) is considered a rare disorder, it is an autosomal recessive phenotype and the frequency of heterozygote subjects might be higher than suspected. The purpose of this study was to assess the prevalence of GS in Japanese and the effects of heterozygous GS mutations on blood pressure levels. We used the TaqMan system to detect 9 Gitelman's syndrome mutations in SLC12A3 that have been reported in Japanese. We then conducted association studies between these mutations and blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…We found 56 subjects heterozygous with the 180K allele, 14 subjects heterozygous with the 569V allele, 1 subject with the 623P allele, 1 subject with the 642C allele, 47 subjects with the 849H allele, and 1 compound heterozygous subject with the 180K and 849H alleles, in total of 1,852 subjects (3). Thus, the combined allele frequency of the GS mutations was 0.0321.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We found 56 subjects heterozygous with the 180K allele, 14 subjects heterozygous with the 569V allele, 1 subject with the 623P allele, 1 subject with the 642C allele, 47 subjects with the 849H allele, and 1 compound heterozygous subject with the 180K and 849H alleles, in total of 1,852 subjects (3). Thus, the combined allele frequency of the GS mutations was 0.0321.…”
Section: Introductionmentioning
confidence: 81%
“…However, almost all of the reported GS mutations were from case reports without functional confirmation (2,3). It is possible that the reported mutations were simply polymorphisms and the true mutations were in linkage with the polymorphisms in the reported pedigree.…”
Section: Discussionmentioning
confidence: 99%
“…All three of these cases showed mild hypokalemia and a case reported by Monkawa et al showed mild hypocalciuria, as seen in the present study. Tago et al recently reported the prevalence of mutations of the TSC gene in Japanese and found that the frequency of GS mutations was 0.0321 [23]. The frequency of mutations causing 180K, 569V and 849V were 1.51, 0.38 and 1.27%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In the test of SLC12A3 gene mutation of GS patients, negative genetic testing could involve large genomic rearrangements that are missed by direct sequencing that usually accounts for 6% of mutations [17]. Reports have indicated that the heterozygous mutations frequency of European and Asian is about 3% and 1% respectively, the morbidity is 1/1000-9/10000 [18,19]. Although the GS patients who have been confirmed by gene mutation are constantly increasing, up to 40% of GS patients carry only a single mutation in SLC12A3 instead of being compound heterozygous or homozygous [17].…”
Section: Discussionmentioning
confidence: 99%